2015
DOI: 10.1371/journal.pntd.0004236
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Potential Indicators of Hospitalized Cases of Neurocysticercosis and Epilepsy in Ecuador from 1996 to 2008

Abstract: BackgroundEpilepsy is one of the most common signs of Neurocysticercosis (NCC). In this study, spatial and temporal variations in the incidence of hospitalized cases (IHC) of epilepsy and NCC in Ecuadorian municipalities were analyzed. Additionally, potential socio-economic and landscape indicators were evaluated in order to understand in part the macro-epidemiology of the Taenia solium taeniasis/cysticercosis complex.MethodologyData on the number of hospitalized epilepsy and NCC cases by municipality of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…Furthermore, in Africa, ignorance surrounding the presence, magnitude and impacts of the parasite by stakeholders and political authorities have led to the disease being often unrecognized and under reported (Assana et al, 2013;WHO 2016a). This is further complicated by scarcity of information on the disease due to lack of overt disease manifestation in many cases in both humans and pigs (Fleury et al, 2015;Ron-Garrido et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Africa, ignorance surrounding the presence, magnitude and impacts of the parasite by stakeholders and political authorities have led to the disease being often unrecognized and under reported (Assana et al, 2013;WHO 2016a). This is further complicated by scarcity of information on the disease due to lack of overt disease manifestation in many cases in both humans and pigs (Fleury et al, 2015;Ron-Garrido et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, that the high rates of comorbidity of NCC and epilepsy are coincidental due to high concurrent prevalence rates of the two conditions, which occur independently from one another, in certain countries [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…The spatial analysis was conducted in SATSCAN v9.6 (Last version March 2018) [48], it searched, tested for significance and identified approximate locations of areas with an increased incidence rate for the occurrence of NCC and four NDPAN, following the methodology described by Ron-Garrido et al [28] and Kulldorff [46] with small modifications for purely spatial analysis. Briefly, the purely spatial analysis used the number of reported cases for each NDPAN distributed by canton together with the total population of the canton and the spatial coordinates of each canton, then, a Poisson distribution was used to compare the number of cases in the scanned locations.…”
Section: Spatial Analysis and Statistical Methodsmentioning
confidence: 99%
“…Previous studies in Ecuador have shown the heterogeneity of the geographical distribution of NCC cases within the country, which should be taken into account in order to avoid over/ underestimation of the real impact of NCC, as well as, for other neglected tropical diseases. Spatial analysis of the distribution of NCC cases and other potentially associated neurological disorders could bring more evidence to the discussion of the role of NCC in the occurrence of CNS disorders in T. solium endemic regions [28].…”
Section: Introductionmentioning
confidence: 99%